Digital holography and its multidimensional imaging applications: a review. (17th February 2018) - Tahara, Tatsuki; Quan, Xiangyu; Otani, Reo; Takaki, Yasuhiro; Matoba, Osamu
Abstract : We introduce digital holographic techniques and recent progress in multidimensional sensing. Digital holography can be used to perform multidimensional imaging of three-dimensional structure, dynamics, quantitative phase, multiple wavelengths, and polarization state of light and sensing of a holographic image of nonlinear light and a three-dimensional image of incoherent light. Abstract: In this review, we introduce digital holographic techniques and recent progress in multidimensional sensing by using digital holography. Digital holography is an interferometric imaging technique that does not require an imaging lens and can be used to perform simultaneous imaging of multidimensional information, such as three-dimensional structure, dynamics, quantitative phase, multiple wavelengths and polarization state of light. The technique can also obtain a holographic image of nonlinear light and a three-dimensional image of incoherent light with a single-shot exposure. The holographic recording ability of this technique has enabled a variety of applications.